Acute effects of whey protein isolate on cardiovascular risk factors in overweight, post-menopausal women - Pal, Sebely; Ellis, Vanessa; Ho, Suleen (Atherosclerosis, 2010)
The purpose of this study was to investigate the acute effects of dietary whey proteins on lipids, glucose and insulin, and resting energy expenditure in overweight and obese post-menopausal women, a population highly susceptible to cardiovascular disease. A three-way crossover design study was conducted where 20 overweight or obese, post-menopausal women were randomised to consume either 45g whey protein isolate, 45g sodium caseinate or 45g of a glucose control in conjunction with a breakfast meal. Blood samples were taken for up to 6h. There was no significant change in postprandial incremental area under the curve (AUC) for total cholesterol, low density lipoprotein, high density lipoprotein, non-esterified fatty acids, Apo B48, insulin and leptin between groups. However, there was a significant decrease in the appearance of triglycerides (TG) in the blood by 21% and 27% after consuming the whey meal compared to control and casein meals, respectively, as measured by AUC. There was also a significant reduction by 27% and 32% in the AUC for TG:ApoB48 ratio in the whey group compared to the glucose and casein groups, respectively. There was a significantly lower AUC for blood glucose after the consumption of the whey and casein meal compared to glucose meal. These findings suggest that a single dose of whey protein can decrease arterial exposure to smaller TG-enriched lipoprotein particles compared to the glucose and casein meals in the postprandial period in overweight and obese, post-menopausal women.